Integrated Student Management Information System / Melissa Malathy Subramaniam - Melissa Malathy, Subramaniam (2001)
ISMIS is a an integrated system designed to provide students information in order to facilitate schools administration, decision-making and monitoring of students' development in curricular and co-curriculum activities. Specially for teachers and school administrators, the purpose of this project is to develop a student information system that contains the information of the students in a school and provide a system that will enable the retrieval of these information that include students' personal particulars, academic and non-academic achievements as well as performance records and all other items pertaining to student matters. The development of ISMIS is divided into three sections, which are curriculum, student affairs and co-curriculum. This report will only focus on Student Affairs modules. ISMIS is presently partially deployed. All rights are reserved for the Faculty of Computer Science and Information Technology, University of Malaya.